Emotional Focused Coping on COVID-19 Survivors During Isolation in a Rural Area in Indonesia - Muslimah, Andi Hanifah; Idris, Fairus Prihatin; Andi Asrina (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2021)
Background: The current condition is uncertain due to the Covid-19 pandemic. It has impacted survivors, so that coping strategy is needed, including emotional-focused coping. Aim: The purpose of the study was to obtain information and deeply examine coping strategies during isolation for COVID-19 survivors in the form of emotional-focused coping. Methods: The research method is quasi-qualitative with a phenomenological approach employing observation, in-depth interviews, and documentation. A purposive sampling technique was used to determine the informants. The informants consisted of 10 regular informants, 2 supporting informants, and 1 key informant. Results: The results of this study, which is based on the measurement of the DASS questionnaire, showed that 3 COVID-19 survivors were experiencing mild depression, 1 person with mild anxiety, 4 people with moderate stress, 2 people with severe stress. Coping strategies based on emotional-focused coping is varied such as watching Korean drama, worship/shalat, positive thinking, playing with children, and watching a comedy movie. In contrast to survivors who are self-isolating at home, in hotels and hospitals, and are still adjusting to acceptance. Conclusion: Coping strategies during isolation for COVID-19 survivors are varied, including using emotional-focused coping. This can reduce psychological health problems when isolated in hospitals, hotels, and at home. Regular counseling is advised.